Use R for data analysis and research - Lillis, David (New Zealand Science Review, 2011)
​The R statistics language and environment for scientific and statistical computing and graphics is a genuine New Zealand success story. While at the University of Auckland during the early 1990s, Ross Ihaka and Robert Gentleman developed the initial version of R, primarily for use as a teaching tool. R is open source software which you can download from the CRAN (Comprehensive R Network) website (http://cran.r-project.org/), and combines a powerful programming language, a comprehensive range of statistical functions, and outstanding graphics.